Paenibacillus gyeongsangnamensis sp. nov., Isolated from Soil - Lee, Hyosun; Chaudhary, Dhiraj Kumar; Kim, Dong-Uk (Journal of microbiology and biotechnology, 2024)
A Gram-stain-positive, aerobic, white-coloured, rod-shaped bacteria, designated as a strain dW9 , was isolated from soil. Strain dW9 was catalase-positive and oxidase-negative. Strain dW9 grew at temperature of 20-37°C and at pH of 5.0-7.0. Phylogenetic and 16S rRNA gene analysis indicated that strain dW9T belonged to the genus with its closest relative being S4 (97.4% sequence similarity). The genome size of dW9 was 7,787,916 bp with DNA G+C content of 51.3%. The digital DNA-DNA hybridization (dDDH) and average nucleotide identity (ANI) values of dW9 with its closest relatives were found to be <22.0% and <74.0%, respectively. The only respiratory quinone was MK-7, and the major fatty acids were antiso-C and iso-C . Overall, the comprehensive taxonomic analysis revealed that strain dW9 met all the fundamental criteria to be classified as a novel species within the genus Accordingly, we propose the name sp. nov., with the type strain dW9 (=KCTC 43431 =NBRC 116022 ).